PENGARUH MICROLEARNING MELALUI PLATFORM VIDEO BERDURASI PENDEK TERHADAP HASIL BELAJAR AUTOCAD DALAM PENDIDIKAN VOKASIONAL - Anggun Zuraidah, Trisuci; Tri Kuncoro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the effectiveness of microlearning delivered via a short-form video platform in improving AutoCAD learning outcomes among vocational students. Although digital learning has been widely adopted, research on the role of social media-based microlearning in the context of technical and procedural learning remains limited. This study employed a quasi-experimental design with a non-equivalent control group involving 63 students from a vocational high school. Data were collected through cognitive tests, practical performance assessments, and affective observations. Statistical analyses included the Wilcoxon Signed-Rank Test, the Mann–Whitney U Test, and calculations of effectiveness using N-Gain. The results indicate that students who participated in microlearning demonstrated significantly better performance compared to the control group, with higher post-test scores and N-Gain values in the moderate category. This intervention effectively reduced cognitive load and improved visual-procedural understanding. This study contributes to digital pedagogy by demonstrating that short-form video platforms can be effectively integrated into vocational education to enhance technical competencies.